Growing with Values - Santos, S.; Fonseca, C. (Open Schools Journal for Open Science, 2020)
This project aims to alert, raise awareness, research and learn from an environmental protection perspective. The project intends to explore the ecosystems and biodiversity, from the school curriculum of different subject areas (Natural Sciences, Mathematics, Portuguese, Citizenship and Artistic Expressions). This is made through the principles of the scientific method, observation, data collection, experimentation, fieldwork, exchange and communication of ideas, as well as cooperation and partnership with different entities. With this project, it is intended to make children observe the surrounding environment, collect information outside the classroom, categorize what they observed and find solutions to real environmental problems. In this way, it is possible to bring students closer to biodiversity issues, such as “Pollination in urban environments”, “Why are there few insects in urban environments?” and "What is the importance of insects for pollination and the balance of ecosystems?"